KELAYAKAN MEDIA AUDIO VISUAL DALAM MENULIS TEKS ANEKDOT SISWA KELAS X SMA N 2 LUBUK PAKAM - Adelia Rafita; Ali Ali; Ratna Soraya (UNIVERSITAS DHARMAWANGSA, 2025)
This study aims to develop and test the feasibility and effectiveness of audio-visual media in improving the writing skills of anecdotal texts of class X students of SMA N 2 Lubuk Pakam. The population of students is 394 students and the sample taken is 36 students, namely class X-F. This type of research is Research and Development (R&D) using the ADDIE model and method adapted and developed by Reiser and Mollenda in the 1990s, namely, analysis, design, development, implementation, and evaluation. The results of this study indicate that audio-visual media in improving the writing skills of anecdotal texts of class X students of SMA N 2 Lubuk Pakam are classified as very feasible. The assessment of the level of validity of audio-visual media by material expert I obtained an average of 92.67% with the qualification